Kepemimpinan Musa dalam Kitab Bilangan dan Implikasinya Bagi Guru PAK - Tresa Marbun (Sepakat : Jurnal Pastoral Kateketik, 2023)
Moses' leadership in the Book of Numbers shows high moral and ethical principles, courage, justice, and the ability to lead and manage people with a long-term vision. Implications for Christian Education Teachers in the modern educational environment include having a clear and measurable vision, strengthening morals and ethics, applying inclusive leadership, and developing adaptation skills to cope with changes and challenges. By applying Moses's leadership principles and the concrete solutions suggested, Christian Education can become an effective leader in facing challenges in the modern education environment.